Predicting daily energy production in a blockchain-based P2P energy trading system - Babakulov Bekzod Mamatkulovich; To’rabekov Muhammad Alisher o’g’li; Yusupov Adxamjon Dilshod o’gli; Abdualimov Akbar Akmal o'g'li (Zien Journals, 2023)
Many governments are reducing conventional energy production using natural gas or coal as they spread much CO2 to into the atmosphere, leading to global warming. Moreso, with a sharp increase in electricity demand, renewable energy sources are gaining more popularity around the world. A renewable energy source such as solar energy offers one of the easiest ways of generating renewable energy as it can be done by anyone/household through the installation of solar panels in an open place such as house roofs. Therefore, deleting the centralized exchange of the generated energy by the household will provide huge economic benefits as well as optimize the flow of renewable energy. However, the current conventional centralized energy trading makes it impossible for individuals (prosumers) to participate because of the need for third parties to enable transactions which in turn adds extra financial burden and discomfort. To eradicate the need for a third party through decentralization while ensuring non-comparability, transparency, security, and integrity of transactions, previous works have proposed the integration of blockchain systems into the trading system. However, to ensure the sustainability of blockchain technology for trading, there is a need to consider energy consumption and prediction in the system to enable planning about the energy demand.
Keywords: consider; consumption; prediction